Efektivitas Pre-Lecture Quiz untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Utami, Esti; Rudibyani, Ratu Betta; Sunyono, Sunyono (FKIP Universitas Lampung, 2018)
Effectiveness of Pre-Lecture Quiz to Improving the Creative Thinking. This research was aimed to describe the effectiveness of Pre-Lecture Quiz to improving student’s creativity thinking skill on Arrhenius acid-base topic. The research method used was quasi experimental with non-equivalen pretest-postest control group design. The sample selection was done by cluster random sampling, obtained XI IPA 3 as experimental class and XI IPA 6 as control class. The effectiveness of Pre-Lecture Quiz was showed by the significant difference for average n-Gain of flexible thinking skill between the experiment and control class, for experiment class was 0.70 with high categorize and for control class was 0.48 with middle cateogorize. The conclusion of this research is effective Pre-Lecture Quiz and has a high effect size to improving the ability of creative thinking on Arrhenius acid-base topic.Keywords: creative thinking, Pre-Lecture Quiz, Arrhenius acid-base DOI: http://dx.doi.org/10.23960/jpmipa/v19i1.pp37-49